New thought experiment to test the generalized second law of thermodynamics - Matsas, GEA; da Silva, ARR (American Physical Soc, 2005)
We propose an extension of the original thought experiment proposed by Geroch, which sparked much of the actual debate and interest on black hole thermodynamics, and show that the generalized second law of thermodynamics is in compliance with it.